The burden of low back pain in children and adolescents with overweight and obesity: from pathophysiology to prevention and treatment strategies - Ambrosio, Luca; Mazzuca, Giorgia; Maguolo, Alice; Russo, Fabrizio; Cannata, Francesca; Vadalà, Gianluca; Maffeis, Claudio; Papalia, Rocco; Denaro, Vincenzo (Therapeutic advances in musculoskeletal disease, 2023)
Nonspecific low back pain (LBP) is one of the most common causes of disability, affecting all individuals at least once in their lifetime. Such a condition is also becoming increasingly frequent in the pediatric population, especially in children and adolescents with overweight/obesity. Furthermore, new-onset LBP during adolescence has been demonstrated to be a strong predictor of developing LBP later in life, contributing to poorer outcomes and increasing social and medical costs. Several causes and different mechanisms have been considered for the development of LBP in pediatric individuals affected by obesity. For this reason, planning adequate prevention and treatment strategies, mainly through conservative lifestyle changes, would be crucial to anticipate the negative consequences of persisting LBP in adulthood. The aim of this narrative review was to characterize the relationship between LBP and overweight/obesity in the pediatric population, highlighting epidemiological and pathophysiological aspects. In addition, prevention and treatment approaches will be reviewed considering the need to reduce the burden of LBP on this population. According to our search, LBP was more frequent in children and adolescents with overweight and obesity and has been associated with several anthropometric and lifestyle factors, including lumbar hyperlordosis, sedentary habits, physical inactivity, carrying a heavy schoolbag, low vitamin D levels, psychosocial ill-being, and premature intervertebral disc degeneration. Most of these conditions may be addressed with conservative strategies mainly consisting of dietary adjustments, physical exercise, education programs, and physical therapy.